Peningkatan Literacy Keuangan Digital dan Strategi Pemasaran Produk Khas Nagari Kecamatan Lembah Gumanti Kabupaten Solok - Sari, Astri Yuza; Putra, Hari Setia; Trinanda, Okki; Cerya, Efni; Thaib, Ilham; Fithrah, Rahmuliani; Ofanto, Ofanto; Arsita, Sari; Ahlunnazak, Ahmad Istiqlal (Universitas Negeri Padang, 2025)
Business environment becoming increasingly competitive, MSMEs are required to enhance their creativity in both production and marketing processes. The MSME Forum Lembah Gumanti has made commendable progress in processing and promoting its products. However, it continues to face obstacles in financial record-keeping, food product innovation, and marketing strategies. This research aims to equip MSME participants with better knowledge in digital financial literacy, innovation of local specialty products, and effective digital marketing practices. The approach involves collaborative brainstorming through Focus Group Discussions (FGDs) that engage academics, industry practitioners, government representatives, and MSME participants, along with practical fieldwork. The outcomes of this initiative are: Improved digital financial literacy among MSME Forum Lembah Gumanti; Development of diversified, longer-lasting processed food products using the region’s top agricultural commodities; and Adoption of user-friendly digital marketing tools and promotional techniques tailored to MSME products.